HIM Exclusive - HIM International - HIM Monthly : Britain's National Gay Magazine. (London : Millivres, 1976)
Fonds Suzan Daniel (FSD)
Periodiciteit : maandelijks
Redactie : 283 Camden High St, London NW1
Vanaf (1976) 1 HIM International
Vanaf (1978) HIM Monthly
VA Gay Times
Engels